(untitled) (TSUL LEGAL REPORT, 2026)
The relevance of the research topic is related to the distribution and development of a new financial instrument, aimed at studying and developing such issues as the features of the object and subject of crimes committed in the circulation of cryptocurrency in our country and in other countries, international cooperation in the field of cryptocurrency circulation and the experience of foreign countries in this direction. These questions are important not only for understanding the relationship between the use of cryptocurrencies by transnational criminals, but also for finding measures to control and prevent such cybercrimes. It is necessary to make one more note, in this final qualification work such terms as cryptocurrency, virtual currency, digital currency and digital cash will be used interchangeably to describe cryptocurrency. In the era of globalization, the accelerated development of technology, it is impossible not to notice and feel the influence of the virtual world. This virtual world, referred to as the Internet, has simplified many life processes. In the recent past, crimes were more local and less transnational.